BELAJAR TUNTAS: Latar Belakang, Tujuan, dan Implikasi - Andewi Suhartini (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
Complete learning concept occurs as a reaction to a learning principle “normal curve”. Complete learning experts observe that each learner have a basic characteristic, but each is able to accomplish his objective subject. The illustration of this achievement, however, cannot be identified in the normal curve, but it can be seen in abnormal curve tends to positive point. According to normal curve principle that is more suitable with effort and activity randomly. Education is not random process. It is an activity with specific object. If the teaching is done effectively, the achievement of learner do not spread such as normal curve. In the vice versa that if education is done unsuccessfully if the learner achievement follows normal curve.